2020
DOI: 10.21203/rs.2.16492/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors associated with high-risk low-level viremia leading to virologic failure: 16-year retrospective study of a Chinese antiretroviral therapy cohort

Abstract: Background: Low level viremia (LLV) often occurs during antiretroviral therapy (ART) against HIV-1. However, whether LLV increases the risk of virologic failure (VF) is controversial because of the non-uniform definitions of LLV and VF. Methods: A long-term first line regimen ART cohort from 2002–2018 from Shenyang, northeast China, was retrospectively studied. All participants were followed up every 3 to 6 months to evaluate the treatment effect. The high-risk LLV subgroups leading to VF (with strict standard… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…For example, a nationwide observational cohort in Sweden found that 9% of the patients had LLV at the end of follow‐up [11], and a study conducted in South Africa reported an LLV proportion of 23% [3]. However, a study from China reported an LLV proportion of 38.7% [22]. Unlike other studies that took proportions of LLV into consideration, we instead focused more on the association between time‐varying LLV and mortality without concretely calculating LLV proportions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a nationwide observational cohort in Sweden found that 9% of the patients had LLV at the end of follow‐up [11], and a study conducted in South Africa reported an LLV proportion of 23% [3]. However, a study from China reported an LLV proportion of 38.7% [22]. Unlike other studies that took proportions of LLV into consideration, we instead focused more on the association between time‐varying LLV and mortality without concretely calculating LLV proportions.…”
Section: Discussionmentioning
confidence: 99%
“…The definition of LLV and VF has been inconsistent in studies to date [9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The main caveat is that most studies included samples with up to 999 HIV-RNA copies/mL, which are actually confirmed cases of VF and introduce uncertainty into the analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of uniformity with regard to definitions of LLV, blips, optimal virological suppression (VS) and VF makes comparisons of results among different studies inconsistent [9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In developed countries, virological suppression is defined as VL < 50 copies/mL [10]. However, approximately 10-30% of patients cannot completely control virus replication [18]. LLV is defined as a plasma VL between 51 and 999 copies/mL, and it is associated with microbial translocation and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…PLWH with LLV should be carefully monitored or switched to other regimens. Clinical response to LLV is greatly delayed, which prolongs the duration of LLV and potential for HIV transmission [18]. The diagnostic standard of LLV and regimen-switching decisions urgently need to be reconsidered.…”
Section: Discussionmentioning
confidence: 99%